Advances towards the completion of the Anthurium Flora of Central America (Araceae, Pothoideae): contribution of thirty-one new species from Guatemala, Costa Rica and Panama - Ortiz, Orlando O.; Croat, Thomas B.; Hormell, Robert; Cedeño-Fonseca, Marco (Phytotaxa, 2020)
In the present paper, we include the description of 31 new species from Guatemala, Costa Rica and Panama (including one from the Panama-Colombia border), which are distributed in eight sections. The sections represented and the number of species per section are as follows: Andiphilum (two), Belolonchium (five), Calomystrium (five), Cardiolonchium (eight), Decurrentia (one), Pachyneurium (eight), Polyneurium (one) and Tetraspermium (one). Additionally, three Central American taxa are now considered to be distinct at the species level and are here elevated to specific rank; Anthurium arcuatum, A. fogdeniorum, and A. copense. Notes on habitat, conservation status, taxonomy and morphology are provided for each species as well as illustrations.